Comparison of diets enriched in stearic, oleic, and palmitic acids on inflammation, immune response, cardiometabolic risk factors, and fecal bile acid concentrations in mildly hypercholesterolemic postmenopausal women—randomized crossover trial. Issue 2 (10th June 2019) - Meng, Huicui; Matthan, Nirupa R; Wu, Dayong; Li, Lijun; Rodríguez-Morató, Jose; Cohen, Rebecca; Galluccio, Jean M; Dolnikowski, Gregory G; Lichtenstein, Alice H
ABSTRACT: Background: Direct comparisons between SFAs varying in chain length, specifically palmitic acid (16:0) and stearic acid (18:0), relative to the latter's metabolic product, oleic acid (18:1), on cardiometabolic risk factors are limited. Objective: The aim of this study was to determine the relative comparability of diets enriched in palmitic acid, stearic acid, and oleic acid on inflammation and coagulation markers, T lymphocyte proliferation/ex-vivo cytokine secretion, plasma cardiometabolic risk factors, and fecal bile acid concentrations. Methods: Hypercholesterolemic postmenopausal women ( n = 20, mean ± SD age 64 ± 7 y, BMI 26.4 ± 3.4 kg/m 2, LDL cholesterol ≥ 2.8 mmol/L) were provided with each of 3 diets [55% energy (%E) carbohydrate, 15%E protein, 30%E fat, with ∼50% fat contributed by palmitic acid, stearic acid, or oleic acid in each diet; 5 wk/diet phase] using a randomized crossover design with 2-wk washouts between phases. Outcome measures were assessed at the end of each phase. Results: Fasting LDL-cholesterol and non–HDL-cholesterol concentrations were lower after the stearic acid and oleic acid diets than the palmitic acid diet (all P < 0.01). Fasting HDL-cholesterol concentrations were lower after the stearic acid diet than the palmitic acid and oleic acid diets ( P < 0.01). The stearic acid diet resulted in lower lithocholic acid ( P = 0.01) and total secondary bile acid (SBA) concentrations ( P = 0.04) than the oleic acid diet. All other outcome measures were similar between diets. Lithocholic acid concentrations were positively correlated with fasting LDL-cholesterol concentrations ( r = 0.33; P = 0.011). Total SBA, lithocholic acid, and deoxycholic acid concentrations were negatively correlated with fasting HDL cholesterol ( r = −0.51 to −0.44; P < 0.01) concentrations and positively correlated with LDL cholesterol:HDL cholesterol ( r = 0.37–0.54; P < 0.01) ratios. Conclusions: Dietary stearic acid and oleic acid had similar effects on fasting LDL-cholesterol and non–HDL-cholesterol concentrations and more favorable ones than palmitic acid. Unlike oleic acid, the hypocholesterolemic effect of stearic acid may be mediated by inhibition of intestinal hydrophobic SBA synthesis. These findings add to the data suggesting there should be a reassessment of current SFA dietary guidance and Nutrient Facts panel labeling. This trial was registered at clinicaltrials.gov as NCT02145936.